"To hear with eyes": Gestures, expressions, rhythms. (3rd April 2022) - Gondar, Jô
Abstract: "To hear with eyes" is a Shakespearean expression used by Masud Khan as the title of his article written in 1971. In this text, Khan recounts the clinical case of a young model who told him certain things, but in whose body, lying on the couch, he saw other things. Khan's article is almost 50 years old, and since then the clinical management of bodily issues and subjective dissociations has become more pressing. We have more and more patients who do not use the couch and who seek our gaze. If Khan privileged the analyst's gaze on the patient's body, we can now broaden this horizon, adding layers to the relationship between body expressions, gestures, and rhythms in the clinical encounter. Non-neurotic patients are very sensitive to this; in the analyst's interventions, what patients perceive is the gesture, rather than the content of what is said. In the same way, we must be attentive to the rhythm of each subject during the sessions of analysis. The more traumatic the subjective process is, the more important are the perception of and respect for the patient's rhythm, as well as the possibility of being able to get in synch with their rhythm.